EXAMINATION OF THE PHYSIOLOGICAL AND BIOCHEMICAL CHANGES AFFECTING NUTRITIONAL REQUIREMENTS THAT OCCUR IN DIFFERENT LIFE STAGES OF FISH - ALI, MA; HUSSAIN, Y; BUTT, AS; ALI, MA; RIZWAN, M; MUNIR, N; KABIR, A; MATEEN, L (Biological and Clinical Sciences Research Journal, 2023)
Fish undergo many physiological and biochemical changes throughout life, each demanding distinct nutritional consideration. This study explores the nuanced relationship between physiological and biochemical changes influencing nutritional requirements in different life stages of fish. The research involved an ethical and comprehensive investigation into various fish species’ embryonic, larval, juvenile, and adult phases. Results demonstrated significant variations in growth rates, emphasizing rapid larval growth and unique reproductive hormone patterns during adulthood. Enzymatic activities reflected stage-specific digestive and metabolic demands, with larval stages exhibiting elevated digestive enzyme activities. Proximate composition analyses showcased protein, lipid, and carbohydrate content fluctuations, illustrating the evolving nutritional needs.